ANALYSIS OF THE USABILITY AND ACCESSIBILITY OF WEBSITES IN VIEW OF THEIR UNIVERSAL DESIGN PRINCIPLES - BADZIO, Błażej; BODZIAK, Agnieszka; BRODAWKA, Bartłomiej; BUCHAJCZUK, Karol; SKUBLEWSKA-PASZKOWSKA, Maria; DZIEŃKOWSKI, Mariusz; POWROŹNIK, Paweł (Applied Computer Science, 2022)
Universal design is a strategic approach for planning and designing both the products and their environment, aimed at making a given product available to the widest number of possible users. It ensures equality for all of them and the opportunity to participate in the society. This concept is also crucial in the process of designing and developing software. The research was conducted with the use of four services, three of them were implemented for the purpose of this study. Two of them took into consideration the principles of universal design, while the others did not. The aim of the study was verification of the level of usability and accessibility of services by means of three independent methods: the LUT (Lublin University of Technology) checklist, an assessment taking into account WCAG 2.0 (Web Content Accessibility Guidelines) standards using the automatic WAVE evaluation tool (Web Accessibility Evaluation Tool) and a device allowing to track the movement of the eye while performing various tasks on websites. The websites were assessed by twenty experts in the field of creating web application interfaces, using the LUT checklist. The time to the first fixation (TTFF) that it took respondents to look at specific website elements was measured using the eye tracker device and iMotions software. All websites were checked by means of the WAVE tool to detect irregularities and non-compliance with universal design standards. The analysis performed clearly indicated that websites that follow the universal design guidelines were more useful, intuitive and accessible for users. It might be concluded that interfaces allow to find necessary information and perform desired actions in a shorter time when prepared in accordance with the principles of universal design.